2012
DOI: 10.1007/s12602-012-9107-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Oral Administration of Probiotic Lactobacilli-fermented Milks on Macrophage Function

Abstract: Six strains of lactobacilli belonging to three species (Lactobacillus casei, Lactobacillus acidophilus and Lactobacillus helveticus) were evaluated for probiotic attributes viz. acid tolerance, bile tolerance and cell surface hydrophobicity. All the six strains exhibited probiotic attributes with considerable degree of variation. Three Lactobacillus strains selected on the basis of probiotic attributes were used for preparing three different fermented milks. In order to evaluate the effect of feeding these pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In accordance with the current legislation, the animal experiments were performed with the approval of the Institutional Animal Ethics Committee, National Dairy Research Institute, Karnal, India. The rats were sacrificed by cervical dislocation at the age of 2 months and the peritoneal cavity macrophages were collected by inserting DMEM and Ham’s F‐12 into the cavity, per Kapila et al ().…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with the current legislation, the animal experiments were performed with the approval of the Institutional Animal Ethics Committee, National Dairy Research Institute, Karnal, India. The rats were sacrificed by cervical dislocation at the age of 2 months and the peritoneal cavity macrophages were collected by inserting DMEM and Ham’s F‐12 into the cavity, per Kapila et al ().…”
Section: Methodsmentioning
confidence: 99%
“…The activation of peritoneal macrophages is one parameter that indicates the stimulation of the systemic immune system but the mechanism used by probiotic strains is still unclear. Several authors observed the increase in the phagocytic activity of peritoneal macrophage after 2, 5 or 8 days of feeding with probiotics cultures (Kapila et al 2007(Kapila et al , 2012Rajpal and Kansal 2009), even after 60 days (Kapila et al 2013). Same effects were perceived with the probiotic Dahi culture namely DI (containing Lact.…”
Section: Effects On Macrophage Function and Leucocyte Countmentioning
confidence: 95%
“…Several authors observed the increase in the phagocytic activity of peritoneal macrophage after 2, 5 or 8 days of feeding with probiotics cultures (Kapila et al . , ; Rajpal and Kansal ), even after 60 days (Kapila et al . ).…”
Section: Systemic Immune Systemmentioning
confidence: 99%
“…The bacterial culture was identified by commercially available API® microorganism identification kit and subsequent 16 s rRNA analysis. The culture was characterized as a probiotic strain after investigation of standard probiotic attributes, viz., acid resistance, bile tolerance, cell surface hydrophobicity, and antimicrobial activity as per methods described previously (Kapila et al 2012;Rammelsberg and Radler 1990). Scanning electron microscopy was performed to visualize adherence of LR to Caco-2 cells (Bernet et al 1993).…”
Section: Methodsmentioning
confidence: 99%